Research on Numerical Simulation of Top-Down Construction Effect of Diaphragm Wall of Deep and Large Foundation Pit under Different Working Conditions in Complex Stratum. (11th April 2022) - Sun, Fuxue; Liu, Mingqing; Zhu, Yunhui; Li, Xiaochun; Ge, Gang
Abstract : In order to study the construction effect of deep and large foundation pit excavation and its impact on the surrounding environment under complex stratum conditions, the deep and large foundation pit of the top-down construction method of shield exit shaft of S2 line of Wenzhou City railway is taken as the research object in this paper. According to the complex geological conditions of deep soft soil layer with underlying inclined rock surface in Wenzhou, the numerical simulation method is used to carry out the related research. The simulation results of the deformation characteristics of the diaphragm wall under two different working conditions which are the same length diaphragm wall and the suspended foot diaphragm wall are compared and analyzed. According to the analysis results, the suspended foot diaphragm wall is determined as the final construction scheme of the diaphragm wall, and it is verified by field measurement. The research results can provide technical support for the construction of similar projects. At the same time, it can also provide basic accumulation for the construction of major projects in Wenzhou.